2018
DOI: 10.3233/cbm-170791
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of YTHDF1 is associated with poor prognosis in patients with hepatocellular carcinoma

Abstract: In China, hepatocellular carcinoma (HCC) is the most commonly diagnosed cancer and the leading cause of cancer death in men, followed by lung and stomach cancer. There was an urgent need to identify novel prognostic biomarkers for HCC. We explored the expression pattern of m6A related proteins in HCC tissues by using TCGA in this study. We found that the m6A 'reader' YTHDF1 was significantly upregulated in HCC and was positive correlated with pathology stage. Kaplan-Meier analysis showed that Lower YTHDF1 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
178
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(190 citation statements)
references
References 40 publications
11
178
1
Order By: Relevance
“…From the results of Figure S1, in the training and validation cohorts, YTHDF1 had a good diagnostic performance. So far, many studies in progress with regard toYTHDF1 in colorectal carcinoma and hepatocellular carcinoma, which was usually regarded as an independent prognostic factor [56][57][58]. However, there has been no related reports on LUAD, and no has been conducted as a diagnostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…From the results of Figure S1, in the training and validation cohorts, YTHDF1 had a good diagnostic performance. So far, many studies in progress with regard toYTHDF1 in colorectal carcinoma and hepatocellular carcinoma, which was usually regarded as an independent prognostic factor [56][57][58]. However, there has been no related reports on LUAD, and no has been conducted as a diagnostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that tumor mutation burden (TMB) is also significantly associated with the susceptibility to anti-tumor immunotherapy, and a higher TMB indicates better prognosis in many cancer types (Peng et al, 2019;Wang and Li, 2019). The m6A-related gene YTHDF1 was also closely related to the prognosis of HCC in the TCGA dataset in a previous study (Zhao et al, 2018). We compared the AUC values of our established nomogram with these biomarkers, and found that the predictive power of the nomogram was superior for 1-, 2-, and 3-year OS in the LIRI-JP dataset (Figure 6).…”
Section: The M6a-related Nomogram Has High Predictive Powermentioning
confidence: 86%
“…Among its physiological roles, YTHDF1 enables translation of m 6 A‐methylated neuronal mRNAs in reaction to neuronal stimulus, which aids to learning and memory . On the other hand, protein expression of YTHDF1 is upregulated in hepatocellular carcinoma (HCC), being associated with tumour cell cycle, base excision repair, DNA replication, RNA splicing and RNA degradation . Lower YTHDF1 expression has been shown better survival of HCC patients .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, protein expression of YTHDF1 is upregulated in hepatocellular carcinoma (HCC), being associated with tumour cell cycle, base excision repair, DNA replication, RNA splicing and RNA degradation . Lower YTHDF1 expression has been shown better survival of HCC patients . YTHDF1 inhibition has reduced translation efficacy of its target transcripts, indicating an efficient role of YTHDF1 in mRNA translation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation